If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13(x + -5) = 5x + -11 Reorder the terms: 13(-5 + x) = 5x + -11 (-5 * 13 + x * 13) = 5x + -11 (-65 + 13x) = 5x + -11 Reorder the terms: -65 + 13x = -11 + 5x Solving -65 + 13x = -11 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -65 + 13x + -5x = -11 + 5x + -5x Combine like terms: 13x + -5x = 8x -65 + 8x = -11 + 5x + -5x Combine like terms: 5x + -5x = 0 -65 + 8x = -11 + 0 -65 + 8x = -11 Add '65' to each side of the equation. -65 + 65 + 8x = -11 + 65 Combine like terms: -65 + 65 = 0 0 + 8x = -11 + 65 8x = -11 + 65 Combine like terms: -11 + 65 = 54 8x = 54 Divide each side by '8'. x = 6.75 Simplifying x = 6.75
| 3x+5(x-14)=26 | | -10--6= | | 3x=-3x+13 | | 4x-6(-5+2x)+30=64-4x | | 42x=30x+-3 | | 5x-30+2x+6= | | 5x+2(2x-15)=15 | | 3p+1=p+5 | | 7.7(x-2)=0.3x+32.6 | | -9x-30+7x=8 | | 3+5n=4(n+2)+6n | | 14+2y=13 | | (10-1x)((3*2)+(7*8))=0 | | 12(x+4)=10x+10 | | -6b=-12 | | 7y-15=4y+6 | | a^2+14a-5=0 | | 13(x+-6)=7x+-15 | | 5(x-6)+2(x+3)= | | 12=6c | | 6x+2y=45 | | 6x+2(7x-15)=70 | | h=(-16t^2) | | 24.1=-13.4+3y | | 2(4+5)+21= | | 21=-7+-h | | -12x-37+6x=53 | | -6=4+30 | | 48--24= | | 3x+2y+z=42 | | 7m-11=-4 | | 2--1= |